2018
DOI: 10.1016/j.bcmd.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic variation in protease activated receptor 4 after an acute coronary syndrome: Analysis from the TRACER trial

Abstract: Variation in platelet response to thrombin may affect the safety and efficacy of PAR antagonism. The Thr120 variant of the common single nucleotide polymorphism (SNP) rs773902 in the protease-activated receptor (PAR) 4 gene is associated with higher platelet aggregation compared to the Ala120 variant. We investigated the relationship between the rs773902 SNP with major bleeding and ischemic events, safety, and efficacy of PAR1 inhibition in 6177 NSTE ACS patients in the TRACER trial. There was a lower rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…Although our report is the largest study to date of the in vitro effects of thrombin on the PAR4 Ala120Thr variant, a larger sample size would enable consideration of other confounding genetic or demographic variables. However, the small but significant association between the rs773902 A allele and ischemic stroke seen in the ~7000 stroke reported in our study (Table 2) and the reduction in bleeding associated with the rs773902 AA genotype seen in ~7000 ischemic coronary patients receiving anti-platelet therapy [14] provide important support for the in vivo importance of this genetic variant. Together with our functional data, these clinical association signals warrant further study, including a rs773902-diabetes interaction.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although our report is the largest study to date of the in vitro effects of thrombin on the PAR4 Ala120Thr variant, a larger sample size would enable consideration of other confounding genetic or demographic variables. However, the small but significant association between the rs773902 A allele and ischemic stroke seen in the ~7000 stroke reported in our study (Table 2) and the reduction in bleeding associated with the rs773902 AA genotype seen in ~7000 ischemic coronary patients receiving anti-platelet therapy [14] provide important support for the in vivo importance of this genetic variant. Together with our functional data, these clinical association signals warrant further study, including a rs773902-diabetes interaction.…”
Section: Discussionmentioning
confidence: 68%
“…Secondly, because thrombin functions as a platelet agonist through both platelet PAR4 and PAR1 [13], and because PAR4 has been shown to heterodimerize with PAR1 [13], it is critical to characterize thrombin-induced PAR4 signaling in human platelets expressing both PAR4 and PAR1. Lastly, acute coronary syndrome patients who are homozygous A for rs773902 exhibited less bleeding in a clinical trial of the PAR1 blocker vorapaxar [14], but a direct effect of the PAR4 variant on platelets inhibited with vorapaxar has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical impact of this change in receptor sensitivity to agonists and/or antagonists, if any, remains unknown, although initial studies suggest some effect. The PAR4 sequence variant affects an individual’s outcome after PAR1 inhibition, with analysis of the TRACER trial for vorapaxar indicating lower rates of major bleeding in patients with the ‘hyper-reactive’ Thr120 PAR4 variant [75]. In addition to effects on PAR1, an individual’s genotype at rs773902 may also impact their response to P2Y 12 inhibitors, with individuals expressing the Thr120 PAR4 variant less sensitive to prasugrel following the percutaneous coronary intervention [76].…”
Section: What Are the Major Issues To Consider For Par4 Inhibitors?mentioning
confidence: 99%
“…Another is a constitutively active receptor. Yet another is an alteration in downstream signal coupling or changes in receptor desensitisation [75]. None of this has been investigated in great detail, but is of clear interest as PAR4 antagonists move forward in their clinical development.…”
Section: What Are the Major Issues To Consider For Par4 Inhibitors?mentioning
confidence: 99%
“…One study has shown a greater risk of thrombosis amongst carriers of the Thr120 in a general American population (Whitley et al, 2018). In addition, the relative benefits and risks of using the PAR1 antagonist vorapaxar may vary according to the PAR4 sequence variant, with a suggestion of lower bleeding rates in Thr120-expressing individuals treated with vorapaxar than in Ala120-expressing individuals (Tricoci et al, 2018). Furthermore, PAR4 antagonists are in clinical development (French and Hamilton, 2017;Wong et al, 2017) and the impact of the rs773902 PAR4 SNP on the efficacy and safety of these agents remains unexplored.…”
Section: Introductionmentioning
confidence: 99%